Flow and heat transfer characteristics of ice slurry in typical components of cooling systems: A review. (October 2019) - Wang, Jihong; Battaglia, Francine; Wang, Shugang; Zhang, Tengfei; Ma, Zhenjun
Highlights: Flow and heat transfer characteristics of ice slurry in cooling systems are reviewed. Experimental, analytical, and numerical approaches used are reviewed. Universal methods are needed to characterize ice slurry flow and heat transfer. Strategies are needed to optimize the operation of cooling systems with ice slurry. Abstract: Ice slurry is attracting increasing attention owing to its high cooling rate, heat transfer capability and energy storage density. This paper provides a state-of-the-art review of ice slurry flow and heat transfer characterization in typical components of cooling systems including pipes, fittings, valves, pumps and heat exchangers by experimental measurements, analytical quantifications and numerical simulations. Generally, the experimental measurements concerned the flow pattern, pressure drop, rheology and heat transfer of ice slurry, and the measurement data were usually used to develop and validate analytical and numerical models. The analytical quantification was commonly performed by the principles of non-Newtonian fluid mechanics, which simplified the multiphase flow into a single-phase flow and can predict the friction factors and heat transfer coefficients. The numerical simulation employed multiphase flow dynamics to establish the governing equations for ice particles and carrier fluids in ice slurry flow and heat transfer with phase change, thus providing predictions on different physical fields of ice slurry flow. It indicated that the experimental measurement, analytical quantification and numerical simulation presented different advantages and disadvantages in describing ice slurry flow and heat transfer. The combination of numerical simulation with the experiment measurement and analytical quantification is promising to improve the performance of each single method in terms of accuracy, efficiency and generality. Moreover, the development of optimization strategies to maximize the performance of cooling system with ice slurry is essential.